Prosesi Ritual Kidungan: Pada Masyarakat Desa Kuthuk Kabupaten Kudus - BAHTIAR, Hafid Zuhdan (PPS ISI Yk., 2017)
Ritual kidungan is one of the ritual still growing in the kuthuk district Kudus. At the beginning of emergence ritual is used for puputan or people often mention with ptup umbilical in infants. But see the meaning of kidung considered have sufficient many of the functions so for now and also used for tradition ngeslupi omah ( pray for a new home ) and also for the family was disaster strike. The study focused on the problems and mantrawedha having differences ways to singing by Kuthuk people. Methods used in this research is qualitative approach case study. An instrument used to analyze use the theory distinction and habitus Bourdieu. Explained that researchers will see and observing the difference a procession ritual kidungan to kuthuk people, who into 2 community groups different namely the public wetan kali and community kulon kali. This theory used to dissect the question why the community wetan kali and kulon kali different in implementing ritual kidungan. Based on the results of the analyses obtained this final conclusion that results from analysis that kuthuk people consisting of the community wetan kali and the community kulon kali different in implementing ritual kidungan because each community groups having different religion. The community wetan kali and the community kulon kali the handling any differences with positives.